Protein K: a new major outer membrane protein found in encapsulated Escherichia coli. - Paakkanen, J (1979)
The protein composition of purified outer membranes of 47 Escherichia coli strains was examined by sodium dodecyl sulfate-polyacrylamide gradient gel electrophoresis. Of 33 encapsulated strains, all contained an outer membrane protein distinguishable from previously reported proteins. The 14 non-encapsulated strains with one exception lacked this protein. Because of its apparent association with encapsulation (K antigen) we have named it K protein. The protein was purified nearly to homogeneity by chromatography in the presence of detergents, and its composition was determined. Its amino acid composition does not differ significantly from that reported for protein I, another E. coli major outer membrane protein. Furthermore, the N-terminal amino acid sequence of protein K indicates that it is related to protein I.